Cover Feature: Nanoscopic Characterisation of Individual Endogenous Protein Aggregates in Human Neuronal Cells (ChemBioChem 19/2018). (21st September 2018) - Whiten, Daniel R.; Zuo, Yukun; Calo, Laura; Choi, Minee‐Liane; De, Suman; Flagmeier, Patrick; Wirthensohn, David C.; Kundel, Franziska; Ranasinghe, Rohan T.; Sanchez, Santiago E.; Athauda, Dilan; Lee, Steven F.; et al.
Abstract : The cover feature picture shows how DNA PAINT can be used with aptamers—short sequences of RNA or DNA that can form a 3D structure that can bind to a target molecule—to generate super‐resolution images of endogenous amyloid aggregates within patient‐derived neuronal cells. The aptamer is modified through the addition of several DNA bases that are complementary to those of a dye‐labelled oligonucleotide. A super‐resolution image is then formed as the dye‐labelled oligonucleotide temporarily hybridises with the aggregate‐bound aptamer (bottom left). Super‐resolution images of fibrils formed from α‐synuclein, the protein associated with Parkinson′s disease, are shown bottom right. More information can be found in the communication by D. Klenerman, M. H. Horrocks et al. on page 2033 in Issue 19, 2018 (DOI: 10.1002/cbic.201800209 ).